Analisis Kualitas Pelayanan dan Lokasi Terhadap Loyalitas Peserta Didik Ypltbi Di Lotte Shopping Avenue Kuningan Jakarta - Jonatan, Jonatan (Journal of Economics & Business UBS, 2019)
The purpose of this study was to determine how much influence the quality of service, location and learners' satisfaction to loyalty learners against two English language institutions in Jakarta. Respondents involved in this study were 78 learners, the method used is non-probability sampling, the sampling pursposive. Data was collected by multiple linear regression using SPSS 23 software. Results of regression showed that the variables of service quality and significant positive effect on loyalty learners towards English language institutions, YPLTBI Lotte Shopping Avenue Kuningan Jakarta, quality of service and location together / simultaneous correlated with loyalty learners.Â This study shows that the loyalty of the students in the institutions of English in Jakarta, YPLTBI Lotte Shopping Avenue Kuningan Jakarta can be influenced by factors of service quality and location of the Loyalty earners.